Strategi Pemasaran Jasa Pendidikan dalam Meningkatkan Nilai Jual Madrasah - Faizin, Imam (Madaniyah, 2017)
Competition in education becomes inevitable, many educational institutions are abandoned by customers so that the negative dynamics of some educational institutions. Meanwhile, Islamic educational institutions, especially madrassas, are still overwhelmed by second-class education institutions with a favorable level under public education institutions. There are still many people who are lacking or even not yet know madrasah. Therefore, many changes have to be made, especially madrasah related to the management pattern. Madrasahs as education service providers need to learn and have a passion for increasing customer satisfaction because education is a circular process that is facing each other and sustainable. The madrasah initiative starts from finding out. In a world full of innovation, competition and expansion, marketing terms need to be redefined. The marketing of educational services in Madrasahs does not necessarily mean commercialization, but prioritizes quality education, and provides excellent service to its stakeholders, thereby providing satisfaction to the community that can be beneficial in increasing the "selling point" of Madrasahs.Â Keywords: Educational Services, Marketing Strategy, Marketing Mix.